2019
DOI: 10.3390/met9080862
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Synchrotron X-Ray Diffraction of Ti-6Al-4V During Thermomechanical Treatment in the Beta Field

Abstract: This work aims to identify the mechanisms of restoration occurring in Ti-6Al-4V during hot plastic deformation and subsequent heat treatment. The allotropic phase transformation that occurs during cooling distorts the interpretation of the restoration mechanisms taking place at high temperatures. Therefore, analysis of deformed samples by conventional microscopy have led to controversies in the interpretation of the main dynamic restoration mechanism. Additionally, static restoration of the microstructure can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The second and third contributions deal with the characterization of nickel-based superalloy [2] and titanium alloys [3] under hot deformation, respectively. In the work of B. Zhang et al [4], a nickel-based superalloy was produced by welding a powder metallurgy superalloy (the rim) with the wrought superalloy (the bore).…”
Section: Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second and third contributions deal with the characterization of nickel-based superalloy [2] and titanium alloys [3] under hot deformation, respectively. In the work of B. Zhang et al [4], a nickel-based superalloy was produced by welding a powder metallurgy superalloy (the rim) with the wrought superalloy (the bore).…”
Section: Contributionsmentioning
confidence: 99%
“…The hot deformation mechanisms and the flow behaviour of the couples are similar to those of the single alloys, with larger activation energies. The work of F. Warchomicka et al [3] deals with the characterization of the evolution of the microstructure of Ti64 alloy using in situ synchrotron diffraction during compression and annealing. The authors demonstrated that dynamic recovery happens during hot deformation and that the recrystallization occurs statically during the heat treatments.…”
Section: Contributionsmentioning
confidence: 99%
“…Fast detectors (up to 20 kHz) have been employed to examine phase evolution under rapid processing [10,[15][16][17][18][19][20][21][22], such as welding and AM processing, and combination with ultrafast imaging provided new insights into the AM process [9,18,22]. Studies with high angular resolution and a relatively large area detector have revealed details of lattice changes for external mechanical and temperature factors [11,[23][24][25][26][27][28]. Our recent report presented an in-situ study of Ni-alloy 718 with a multi-panel area detector with an unprecedented combination of high 2θ-angular resolution and a 250 Hz frame rate [29].…”
Section: Introductionmentioning
confidence: 99%
“…Analyses using these techniques are not always complete or easily carried out and interpreted. However, the development of high-energy X-ray diffraction (HEXRD) using synchrotron radiation allows real-time (in situ) observation of microstructural evolution and phase transformations [3,6,10,11,13,14]. HEXRD presents the advantage of short acquisition times and high resolution, and for this reason has gained momentum in the metallurgy area for providing the possibility of precisely elucidating phase transformation phenomena [11,12,15].…”
Section: Introductionmentioning
confidence: 99%